Pesantren, Perempuan, dan Subaltern dalam Perempuan Berkalung Sorban dan Hati Suhita - Novi Diah Haryanti; Farah Nur Fakhriyah (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2021)
This study aims to describe the phenomenon of matchmaking among pesantren. Abidah El Khalieqy's novel Perempuan Berkalung Sorban and Khilma Anis' Hati Suhita are the objects of study. The method used is descriptive qualitative. The data collection technique is done by analyzing the data interpretation. The type of data collected is a library. The approach used is sociology of literature. The data discussed in this study include: (1) comparison of the narrative structure of the two novels above, (2) matchmaking at the pesantren in the two novels, (3) matchmaking between two people and two pesantren, and (4) marriage satisfaction.Research result show Matchmaking in pesantren is usually done because of the interests or goals that benefit one of the parties. MatchmakinginThe two novels originated from compulsion that led to divorce and sadness, especially on the part of women.